Can clinical factors be used as a selection tool for an organ-preserving strategy in rectal cancer?. (2nd August 2016) - Joye, Ines; Debucquoy, Annelies; Fieuws, Steffen; Wolthuis, Albert; Sagaert, Xavier; D'Hoore, André; Haustermans, Karin
Abstract: Background: Rectal cancer patients who achieve a good response to chemoradiotherapy (CRT), may be offered less invasive surgery or even no surgery at all. Implementation of such a policy, however, requires precise patient selection. This study identifies pretreatment clinical factors that are associated with pathological complete response (pCR) and ypT0-1N0 and evaluates their performance as a selection tool for organ-preserving strategies. Material and methods: Patients with rectal cancer treated with CRT and total mesorectal excision between January 2000 and December 2014 were retrospectively included. Following clinical characteristics were extracted from the medical files: age, gender, body mass index, ASA score, cT-stage, cN-stage, distance from the anal verge, pretreatment carcinoembryonic antigen (CEA), pretreatment hemoglobin and distance from the mesorectal fascia. Univariable and multivariable binary logistic regression models were used to predict pCR and ypT0-1N0. The discriminative ability of the prediction models was evaluated by receiver operating characteristic analysis. Results: A total of 620 patients were included of whom 120 experienced a pCR (19%) and 170 patients achieved ypT0-1N0 response (27%). A low pretreatment CEA, a high pretreatment hemoglobin and a high cN-stage were associated with pCR in multivariable analysis. A low pretreatment CEA, a low cT-stage and a high cN-stage were associated with ypT0-1N0. After cross validation, the area under the curve for the pCR and ypT0-1N0 prediction model equaled 0.609 and 0.632, respectively. Conclusion: Despite their statistical significance, the value of pretreatment clinical variables in the prediction of pCR and ypT0-1N0 is very limited. To safely select patients for organ preservation, other strategies need to be explored.